1971
DOI: 10.1149/1.2407807
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometric Disorder in Single Crystalline MnO

Abstract: The electrical conductivity of single crystalline manganous oxide was investigated over the temperature range of 900°–1150°C while in thermodynamic equilibrium with oxygen partial pressures of 10−6–10−21 atm. Results indicated that normalMnO may be either p‐ or n‐type. Slopes of 1/6 and −1/6 are obtained from the log σ vs. log PO2 data for the p‐ and n‐type regions, respectively. Thermogravimetric measurements at thermodynamic equilibrium support the evidence of the electron mobility being much greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Additionally, conduction in MnO is electronic, with holes dominating at high oxygen activities and electrons dominating at low oxygen activities [68], [70]. Though further studies will need to be completed to explore the dominant point defects that occur specifically in MnO nanocrystals, the following discussion explores point defect balance via Kroger-Vink notation.…”
Section: Ion Effective Ionic Radii (Pm) Coordination Numbermentioning
confidence: 99%
“…Additionally, conduction in MnO is electronic, with holes dominating at high oxygen activities and electrons dominating at low oxygen activities [68], [70]. Though further studies will need to be completed to explore the dominant point defects that occur specifically in MnO nanocrystals, the following discussion explores point defect balance via Kroger-Vink notation.…”
Section: Ion Effective Ionic Radii (Pm) Coordination Numbermentioning
confidence: 99%
“…Kofstad [16] and Eror and Wagner [17] have shown clearly that the MnO oxide growth mechanism was different in conditions of low oxygen, partial pressure, and low temperature. Recently, Li and Penner [18] studied the diffusion of ZnO into Alumina in a nanowire ZnO/Al 2 O 3 diffusion couple and observed that the spinel formation resulted in the formation of a hollow nanotube.…”
mentioning
confidence: 99%